Analysis of Growth Rate, Effectiveness, Potential, and Contribution of Advertising Tax to Regional Original Revenue (PAD) in Mataram City at 2019-2023: Scoping Literature Review - Addini Nurizzati; Abdul Manan; Siti Fatimah (Future Tecno-Science Publisher, 2025)
This study is a literature review study that aims to examine and analyze various research results related to the growth rate, effectiveness, potential, and contribution of advertising tax to Regional Original Income (PAD) in various regions, with the main focus on Mataram City. Advertising tax as part of regional taxes has a strategic role in supporting regional financing, but its contribution to total PAD is still often found to be relatively low. This study was conducted by reviewing nine relevant previous studies, using a thematic analysis approach to the findings, methods, and conclusions of each study. The results of the study indicate that the effectiveness of advertising tax tends to be high in several regions, but its contribution to PAD is still relatively low. The potential for advertising tax revenue has not been fully utilized, due to weak supervision, lack of tax object data collection, and suboptimality in determining advertising rental values. By identifying common patterns and challenges that often arise, this study provides recommendations for strengthening regulations, developing technology-based collection systems, and increasing institutional capacity in order to optimize advertising tax as a source of PAD.